I. Nilai Multikultural INTEGRASI NILAI MULTIKULTURAL DALAM PEMBELAJARAN PKn UNTUK MENGATASI PENGGUNAAN KATA YANG TIDAK SOPAN DI SMP NEGERI 34 SURABAYA: INTEGRASI NILAI MULTIKULTURAL DALAM PEMBELAJARAN PKn UNTUK MENGATASI PENGGUNAAN KATA YANG TIDAK SOPAN DI SMP NEGERI 34 SURABAYA - nur khofifatuz zuhriyah Khofifa; Muhammad Turhan Yani (Universitas Negeri Surabaya (Unesa), 2026)
This study aims to analyze the integration of multicultural values in Civic Education (PKn) learning to address the use of impolite language at SMP Negeri 34 Surabaya. This research originated from the phenomenon of students frequently using impolite language, which can disrupt the learning atmosphere and social relationships within the school. The focus of this study lies in two main aspects: the strategies employed by Civics Education (PKn) teachers in implementing multicultural values, and students’ experiences related to the use of inappropriate language during classroom activities. The study is limited to Civics Education learning, emphasizing the values of humanism, democracy, and pluralism. Based on observations and interviews, it was found that PKn teachers successfully integrated multicultural values through discussion methods, case studies, and exemplary communication practices. Students showed increased awareness in language use; they began to abandon the habit of speaking impolite and became more careful in choosing words. Multicultural-based Civics Education learning proved effective in creating an inclusive classroom atmosphere that appreciates diversity. From these findings, it can be concluded that the application of multicultural values in Civics Education is effective in reducing impolite verbal behavior in school. Therefore, it is recommended that Civics Education teachers consistently instill multicultural values, and that schools support this effort by fostering a positive culture that respects differences and strengthens students’ character.